Modern derivatives in Islamic perspectives in Pakistan: Shari'ah issues on current Islamic derivative practices. Issue 2 (15th September 2020) - Meo, Muhammad Saeed; Durani, Farah; Kouser, Robina; Haris, Muhammad; Iram, Tahira
Abstract : This study examines the opinions of Shari'ah intellectuals' about Islamic derivatives. This research utilizes a qualitative approach to figure out better comprehension of Shari'ah intellectuals (scholars) views regarding Islamic derivatives. Therefore, five Shari'ah intellectuals were interviewed during this study and these scholars were actively involved in the decision making of Islamic financial institutions in Pakistan. The findings of the study confirm that the consideration of derivative instruments in the Islamic financial industry is significant due to the need for hedging and risk reduction within Islamic financial institutions. This article is among the scanty researches that evaluate Islamic derivatives from the outlook of Shari'ah issues in Pakistan. This study is helpful for the policymakers regarding Islamic derivatives.